Chemotherapy in COVID-19 pandemic: to give or not to give? - Pathak, Abhishek; Ranjan, Subhash; Rathore, Anvesh; Kapoor, Rajan; Gupta, Alpana (International Journal of Advances in Medicine, 2020)
COVID-19 is a new pathogen for humans, not much is known how it affects cancer patients, but definitely there is high risk for cancer patients contracting this disease. So to find a solution to this very challenging situation the oncologists need to formulate certain guiding principles for cancer treatment in this pandemic era. Authors have divided this cancer patients into four categories depending upon the urgency of giving chemotherapy. The lowest priority being Priority A where delaying chemotherapy till this pandemic gets over will not harm the patients much and the highest priority being given to Priority D where authors do not want even a delay of days/ week. It is Priority B and C where the decision needs to made by the clinicians. However, in case authors decide to give chemotherapy in present setting there are certain changes that needs to be made both on patient as well as the hospital end. Like higher degree of awareness among patients, rational usage of resources of the hospital etc. It is indeed a very difficult time for cancer patients who are trying to cope up with malignancy and for most of them; the coronavirus is an extra concern and worry. Till the time authors learn how best treat and care to this patients during this pandemic era do what you can do to keep you and your family stay safe and Healthy.